Age-related macular degeneration with choroidal neovascularization in the setting of pre-existing geographic atrophy and ranibizumab treatment. Analysis of a case series and revision paper - Amaro, Miguel Hage [UNIFESP] (2012)
Purpose: To report the response of choroidal neovascularization (CNV) to intravitreal ranibizumab treatment in the setting of age-related macular degeneration (AMD) with extensive pre-existing geographic atrophy (GA) and a revision paper. Methods: This is a revision paper and a retrospective case series of 10 eyes in nine consecutive patients from a photographic database. The patients were actively treated with ranibizumab for neovascular AMD with extensive pre-existing GA. Patients were included if they had GA at or adjacent to the foveal center that was present before the development of CNV. The best corrected visual acuity and optical coherence tomography (OCT) analysis of the central macular thickness were recorded for each visit. Serial injections of ranibizumab were administered until there was resolution of any subretinal fluid clinically or on OCT. Data over the entire follow-up period were analyzed for overall visual and OCT changes. All patients had been followed for at least 2 years since diagnosis. Results: The patients received an average of 6 +/- 3 intravitreal injections over the treatment period. Eight eyes had reduced retinal thickening on OCT. On average, the central macular thickness was reduced by 94 +/- 101 mu m. Eight eyes had improvement of one or more lines of vision, whereas one eye had dramatic vision loss and one had no change. The average treatment outcome for all patients was -0.07 +/- 4.25 logMAR units, which corresponded to a gain of 0.6 +/- 4.4 lines of Snellen acuity. The treatment resulted in a good anatomic response with the disappearance of the subretinal fluid, improved visual acuity, and stabilized final visual results. Conclusion: The results of this case series suggest that the use of an intravitreal anti-vascular endothelial growth factor (VEGF) agent (ranibizumab) for CNV in AMD with extensive pre-existing GA is effective. Our results are not as striking as published results from large-scale trials of anti-VEGF therapy for subfoveal CNV, presumably due to the limitation in the baseline visual acuity caused by the underlying GA. The good anatomic response with the disappearance of the subretinal fluid, improved visual acuity, and stabilized final visual results were consistent with other ranibizumab studies.